Pengaruh Biaya Produksi dan Biaya Promosi Terhadap Laba Bersih (Studi Pada Perusahaan Roti PT. Nippon Indosari Corpindo Tbk Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2019) - Yulianus Viki Antono; Hendrik Suhendri; Sri Andika Putri (INVENTORY: JURNAL AKUNTANSI, 2021)
The purpose of this research is to find out the influence of production costs and promotional costs on net income at PT NIC Tbk which has been listed on the IDX for the 2014-2019 period. Meanwhile, in this research, quantitative methods are used and multiple linear regression analysis is used. The results found in this research are that the production cost variable can have a significant effect on net income, which can be proven through the value of t count = 7.299 (greater than t table = 2.447) and significant value = 0.000 (smaller than t table = 2.447) 0.05), so that hypothesis 1 can be accepted, while the promotion cost variable can also have a significant effect on net income, it can be proven through the t count = 5.881 (greater than t table = 2.447) and the significant value = 0.000 (less than 0.05), so hypothesis 2 can be accepted. The variable influence of production costs and promotion costs has a significant influence on the net profit of PT NIC Tbk which has been listed on the IDX for the 2014-2019 period of 20.8%.